Investigating the decline of the Martial Eagle (Polemaetus bellicosus) in South Africa - Cloete, Daniël (Percy FitzPatrick Institute of African Ornithology, 2014)
The Martial Eagle (Polemaetus bellicosus) is an African endemic that occurs over a wide range of habitats but at naturally low densities. There is concern throughout its range that it is declining and it now appears to be strongly reliant on protected areas. It is classified globally as Near Threatened by the IUCN with a current consultation underway to up-list it to Vulnerable or Endangered. In this project I describe and explore the decline of the species across South Africa, using data from two repeated national bird surveys - South African Bird Atlas Projects (SABAP 1: 1987-1993; SABAP 2: 2007-2012). These analyses suggest a relatively uniform decline across South Africa in Martial Eagle reporting rates of 59% over the last 20 years. Alarmingly, these declines also occurred in protected areas, including the traditional strongholds of the Kruger National Park (54% decline) and the Kalahari National Park (44% decline). Independent survey data, undertaken in the Kalahari National Park, confirmed these declines and reinforced the validity of using the two SABAP surveys to examine population change. Within protected areas, the species is still encountered five times more frequently and is six times as abundant as compared to outside protected areas. Between the biomes, the species is encountered the least and has the lowest abundance in the Grassland biome where tree density is low, and has the highest abundance in the Savanna biome where tree density is higher. Examining environmental correlates of these population changes provided some support for two hypotheses on the causes of these declines, with climate change (increases in temperature) and power line densities negatively associated with changes in reporting rates. Although this analysis also suggested support for declines being associated with avian prey declines, this was unlikely to be a major driver nationally, because I found that overall avian prey species actually increased over this time period. Within Kruger National Park changes in reporting rates were negatively associated with Elephant densities, which may be related to a reduction in nesting opportunities (large trees) for the species. These results are an initial attempt to assess the broad drivers of decline and should help focus and prioritize further detailed research to elucidate the mechanisms behind this species decline.